2002
DOI: 10.1016/s0735-1097(01)01786-7
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activation markedly reduces endothelium-dependent, flow-mediated vasodilation

Abstract: Sympathetic stimulation, at a clinically relevant range, significantly impairs the FMD response by an alpha-adrenergic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
233
7
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(263 citation statements)
references
References 36 publications
19
233
7
4
Order By: Relevance
“…EAT related to endothelial dysfunction assessed by flow-mediated dilatation of the brachial artery, in patients with metabolic syndrome (MS) (Aydin et al 2010). Furthermore, increased sympathetic activation and decreased vagal activity may markedly suppress endothelial function (Hijmering et al 2002;Huang et al 2004). Şengül and Duman (2011) reported that EAT was significantly associated with blunted heart rate recovery in patients with MS. A recent study revealed a linear and negative correlation between aortic diameters and endothelium dependent vasodilation (Medina et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…EAT related to endothelial dysfunction assessed by flow-mediated dilatation of the brachial artery, in patients with metabolic syndrome (MS) (Aydin et al 2010). Furthermore, increased sympathetic activation and decreased vagal activity may markedly suppress endothelial function (Hijmering et al 2002;Huang et al 2004). Şengül and Duman (2011) reported that EAT was significantly associated with blunted heart rate recovery in patients with MS. A recent study revealed a linear and negative correlation between aortic diameters and endothelium dependent vasodilation (Medina et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Flow-mediated dilation is commonly used for this purpose, but measures mostly the role of eNO in conduit arteries and may be influenced by sympathetic tone. 12 Forearm blood flow responses to intrabrachial infusion of endothelial-dependent vasodilators are also used for this purpose. This approach provides important information about endothelial function, 25 and forearm responses correlate with those of other vascular beds, most notably the coronary circulation.…”
Section: Discussionmentioning
confidence: 99%
“…11 This response, however, seems to be influenced by sympathetic activity. 12,13 Therefore, it is difficult to estimate how important eNO is to overall blood pressure regulation from the use of these conventional methods.…”
mentioning
confidence: 99%
“…In particular, several lines of evidence suggest that NO tonically suppresses sympathetic tone (22,31), and impaired NO function could contribute to the sympathetic activation observed in hypertension. Conversely, sympathetic activation can impair NO function (9). It is possible, therefore, that these interactions between NO and the sympathetic nervous system, rather than a primary impairment of NO-mediated dilation, contribute to hypertension.…”
mentioning
confidence: 99%